THE ROLE OF MICROTRAUMA IN THE DEVELOPMENT OF BACTERIAL CORNEAL ULCERS - A. I. Hazamova; E. N. Verigo; E. V. Chentsova (Oftalʹmologiâ)
Purpose: To study the role of corneal  microtrauma in the development of complications, leading to bacterial ulcers. Performed clinical assessment, conservative therapy, and surgical  interventions for 236 patients with the  complication  of microtrauma, mainly related to  the  prolonged  presence of foreign bodies  in the  cornea (86.1% they  had  a  metallic  nature). Methods included  ophthalmologic investigations  and  laboratory  procedures, which revealed  the  presence of bacterial corneal  ulcer  in 97 cases (41.1%), recurrent erosion  — 62  cases (26.3%), traumatic keratitis — 25 cases (10.6%) and  deep  cornea’s infiltrate  — 52  cases  (22.0%). The development of complications was  due to the  later  removal  of FB (in some  cases more  than  1 month  after  the  trauma), incomplete removal of foreign bodies,  non-compliance  with aseptic and antiseptic rules  during in the removal of FB’s without follow up of patients. Streptococcus,  staphylococcus, pneumococcus, and  isolated  cases of Pseudomonas aeruginosa and  Escherichia  coli were  mainly diagnosed. Conservative therapy  included specific, pathogenetic, symptomatic and antiallergic medications. Nitric oxide (NO) in the gas stream was used  to accelerate the reparative processes, weakening  of the inflammatory exudation and cellular proliferation.  Surgical interventions  were  performed for  preserving  of eyes,  prophylactic  and  therapeutic purposes in the  form  autoconjunctiveal  plast y, deep  lamellar  and  penetrating keratoplast y  (preserved  and  fresh  corneas) and  amniotic  membrane transplantation. According  to the results of treatment of 236 patients with the corneal  erosion  completed with elimination of inflammatory reaction, restoration of corneal  transparency; 52 patients with corneal  infiltrate -development  of opacities  in the stromal cornea layers;  patients with keratitis –formation of corneal  leucoma  and 52%  — keratoplast y were  performed. In cases of corneal  ulcer process ended  with the formation of a  rough  leucoma  in 30 patients (30.9%), surgical  interventions  with a  partial  improvement of visual function  were  observed  in 62 patients (63.9%), the removal of the eye were  done in 5 patients (5.2%).